2022
DOI: 10.1155/2022/6435431
|View full text |Cite
|
Sign up to set email alerts
|

Chelerythrine Inhibits Stemness of Cancer Stem-Like Cells of Osteosarcoma and PI3K/AKT/mTOR Signal

Abstract: Chelerythrine (CHE) is widely found in many herbs and is the main alkaloid constituent of Toddalia asiatica (L.) LAM. It has been proved to exert remarkable antitumor, antifungal, anti-inflammatory, and antiparasitic effects. In osteosarcoma, CHE is reported to inhibit proliferation and promote apoptosis. However, the effect of CHE on cancer stem-like cells (CSCs), which contribute to metastasis and recurrence in osteosarcoma, is still largely unknown. In this study, we investigated the effects of CHE on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Compound Chinese medicine Associated OS cell lines References PI3K/AKT pathway Alantolactone Aucklandia lappa Decne. U2OS, HOS [84] Chelerythrine Toddalia asiatica L. U2OS, MG-63 [85] Andrographolide Andrographis paniculata U2OS [86] Rhaponticin Rheum palmatum L. MC3T3-E1, MG-63 [87] Wnt/β-catenin pathway Piperine Piper nigrum L. U2OS, 143B [88] Icariin Epimedium brevicornu Maxim. 143B [89] Isoquercitrin Bidens pilosa L. 143B, U2OS [90] Polydatin Reynoutria japonica Houtt.…”
Section: Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Compound Chinese medicine Associated OS cell lines References PI3K/AKT pathway Alantolactone Aucklandia lappa Decne. U2OS, HOS [84] Chelerythrine Toddalia asiatica L. U2OS, MG-63 [85] Andrographolide Andrographis paniculata U2OS [86] Rhaponticin Rheum palmatum L. MC3T3-E1, MG-63 [87] Wnt/β-catenin pathway Piperine Piper nigrum L. U2OS, 143B [88] Icariin Epimedium brevicornu Maxim. 143B [89] Isoquercitrin Bidens pilosa L. 143B, U2OS [90] Polydatin Reynoutria japonica Houtt.…”
Section: Signaling Pathwaymentioning
confidence: 99%
“…Chelerythrine (CHE) is widely present in many herbs and is the main alkaloid component of Toddalia asiatica (L.) LAM with significant anti-tumor, anti-fungal, anti-inflammatory and anti-parasitic effects. Chen et al [85] found that CHE significantly inhibited the stemness of OS cancer stem cell markers (including Nanog, Oct4 and nestin) by regulating the PI3K/AKT/mTOR signaling axis, and also decreased the expression of MMP-2/9 protein, so as to inhibit the malignant behavior of CSC. In addition, intervention with CHE also reversed the resistance of OS cells to chemotherapeutic agents (including doxorubicin, methotrexate and so on).…”
Section: Targeted Therapy Of Os By Signaling Cascade Associated With ...mentioning
confidence: 99%
“…Therefore, exploring ways to enhance the anti-tumour activity of PTEN may lead to a new targeted therapy for OS. Chamomine can inhibit the PI3K/AKT/mTOR signaling pathway, weaken the expression of MMP-2/9, and inhibit the invasion and metastasis of OS [107] . It has been reported that 200 μm arbutin significantly inhibited the activity of OS cells, which resulted in a significant increase in the expression of miR-338-3p and a corresponding significant decrease in the expression of MTHFD1L [108] .…”
Section: Signal Pathways Affecting the Process Of Glucose Metabolism ...mentioning
confidence: 99%
“…Recently, it was found that Glaucocalyxin A can induce apoptosis in osteosarcoma cells by increasing the ratio of Bax to Bcl-2, triggering reactive oxygen species (ROS) generation, decreasing mitochondrial membrane potential and inducing caspase-3 and caspase-9 cleavage, as found by using PI3K activators and inhibitors This function of Glaucocalyxin A is mainly achieved by inhibiting the nuclear translocation of GLI1 through the regulation of PI3K/AKT pathway ( Figure 2F ) ( 99 ). Furthermore, it has been found that inhibition of the PI3K/AKT/mTOR signaling pathway promotes apoptosis in osteosarcoma cells induced by chemotherapeutic agents, including DOX and methotrexate (MTX) ( Figure 3A ) ( 124 ). This finding has positive implications for contributing to the current challenge of chemoresistance.…”
Section: Pi3k/akt Pathway In Osteosarcomamentioning
confidence: 99%
“… (A) After being cocultured using CHE with DOX or MTX, apoptosis was measured by performing Annexin V-FITC/PI double staining followed by flow cytometry assay ( 124 ). (B) The apoptosis ratios for each group (percentage of Annexin V+ cells) were determined by flow cytometry ( 125 ).…”
Section: Pi3k/akt Pathway In Osteosarcomamentioning
confidence: 99%